Prevalence of overweight and obesity in the hebiatria outpacient clinic: relationship with childbirth (Research, Society and Development, 2020)
In Brazil, there is a high prevalence of overweight and obesity in children and adolescents. In view of this growth, the objective was to identify the nutritional profile of adolescents in Serra Catarinense. The methodology was a cross-sectional, retrospective, quantitative and descriptive study based on the evaluation of the medical records of patients seen at the outpatient clinic of Hebiatria at the Children's Hospital of reference in Serra Catarinense from March 2014 to February 2018. The indicators used were: the body mass index (BMI), sex, age and mode of delivery used at birth. The analyzes were performed using the Statistical Package for the Social Sciences SPSS® statistical software. Of the total medical records analyzed: 60.4% patients were female, of these 41% were overweight and 59% were obese. In males, it was 20% and 80% respectively. The age group with the largest number of individuals with weight problems is 15 years old. No significant relationship was found between the mode of delivery and weight problems, nor was there an increase in BMI with increasing age. It is essential to carry out further studies to identify the causes and prevent this comorbidity.